Технология самолетостроения учебник для авиационных специалностей вузов - Абибов А. Л. Ашот Леонович; Бирюков Н. М. Николай Михайлович; Бойцов В. В. Василий Васильевич; Григорьев В. П.; Зернов И. А. (Москва, Машиностроение, 1982)
Авт. указаны на обороте тит. л.